The learning engineering toolkit evidence-based practices from the learning sciences, instructional design, and beyond - Goodell, Jim; Kolodner, Janet; Dede, Christopher 1947- (Routledge, 2023)
"The Learning Engineering Toolkit is a practical guide to the rich and varied applications of learning engineering, a process and practice that synthesizes the learning sciences with human-centered engineering design methodologies and data-informed decision-making to support learners and their development. As learning engineering becomes an increasingly formalized discipline and practice, new insights and tools are needed to help education, training, design, and data analytics professionals iteratively develop, test, and improve complex systems for engaging and effective learning. Written in a colloquial style and full of collaborative, actionable strategies, this book explores the essential foundations, approaches, and real-world challenges inherent to ensuring participatory, data-driven, learning experiences across populations and contexts"--...
Includes bibliographical references